Insights into The Diversity of Nepenthes L. (Nepenthaceae) Across Peninsular Malaysia, Including The First Sighting of an Undescribed Taxon with Flared Peristomes and Quadruple-Row Ventral Wings - Tamizi, Amin-Asyraf; Mohamad, Salasiah; Shakri, Mohamad-Alias; Mohd-Rusli, Nurshahidah; Mat-Amin, Noriha; Mohamad-Jamali, Muhamad-Arif (Journal of Sustainable Natural Resources, 2023)
The discoveries of six taxa between 2019 and 2022 have brought the total number of Nepenthes species occurring in Peninsular Malaysia to 18. This article serves as a comprehensive overview, incorporating the latest information and taxonomic insights concerning all species native to the peninsula. The information is derived from published taxonomic records and cumulative field observations conducted since 2013. Notably, it further reports heretofore undocumented discoveries, making it a significant contribution to the current knowledge of tropical pitcher plants. These include a sighting of a population of Nepenthes with unusual traits in the upper montane forest of Banjaran Titiwangsa, which may represent the 19th taxon in Peninsular Malaysia. The plants exhibit conspicuously expanded peristomes and an unusual wing morphology, which altogether provide compelling evidence supporting the recognition of these individuals as a distinct and previously unknown species. Therefore, a provisional taxonomic name—Nepenthes sp. Titiwangsa (pesonawangsa_223) A. Amin—is assigned. The species is inferred to belong to the N. macfarlanei group based on its toothed peristome and the presence of fine hairs below the lid. The partial description, species note, photographs, and a dichotomous key of the proposed new species are provided. In addition, a velvety N. sanguinea population has been observed in northern Banjaran Titiwangsa and treated as a new natural variation (var. velutina) in this article